“EFEKTIVITAS PEMANFAATAN APLIKASI WHATSAPP DALAM PENGAMBILAN KEPUTUSAN REDAKSI” (Studi : Redaksional Harian Rakyat Maluku) - MARLEEN MUSKITA (BADATI, 2020)
This research was conducted to determine the extent of the effectiveness of the use of Whatsapp applications in editorial decision making. The purpose of this research is to find out and analyze the utilization of whatsapp applications in newspapers, especially the People's Daily Editor of Maluku. This research uses a qualitative approach with the type of research used is a descriptive approach.          The use of whatsapp is very effective in editorial decision making in the Maluku People's Daily print media because many journalists are chasing deadlines so that they do not have much time to conduct editorial meetings face-to-face, and are done through the whatsapp group. The use of whatsapp is very effective for the acquisition of information and the division of reporting and evaluation tasks in the Maluku People's Daily.